Basic Biodegradability Assessments (Aerobic /Anaerobic) - Said A. A. Saad; Faeza Mharb; Mahboba Aldareh (African Journal of Advanced Pure and Applied Sciences, 2024)
Biodegradation is a biological process when the organic compounds are broken down into smaller compounds and the responsible for this process is the enzymes, which are produced by microorganism that is living in the environment. The biodegradation is possible to occur in presence of oxygen (aerobic) or without oxygen (anaerobic), but the final product of the degradation is often carbon dioxide or methane. In this study Sample was used is grass. The sample went through a number of chemical analysis test to know the organic and inorganic contents. These tests are Total Dry Matter by Oven Drying for Overnight at 100°C. Total Ash in Forages. ADF (determination of acidic detergent fibers), NDF (determination of neuronal detergent fibers), ADL (Determination of Acid Detergent Lignin), Kjeldahl method to measure crude protein and nitrogen in the sample. Anaerobic digestion was carried out using a simple method to investigate if the sample is able to degrade and produce CH4 and CO2. GC was used to measure the quantity of gas produced. Measured the pH for each bottle. The results shows the percentages of total DM, total of ashes, NDF, ADF, ADL, where % DM (27.19) , Ashes % (12.97) ,%NDF (65.33), %ADF(56) ,%ADL(8) also shows the percentages of crude protein and nitrogen which determined by Kjeldahl Method, where the average of crude protein was 50.03% and nitrogen was 8.00% ,shows the reading of the volume of gas produced over nine days.